The Norwegian system for wild reindeer management — major development since the 19th century - Bråta, Hans Olav (Rangifer, 2003)
In the 19th century the hunting of wild reindeer was relatively unrestricted in Norway. This, combined with a more efficient hunting, caused a severe reduction in the number of wild reindeer at the turn of the century. The national authorities responded by stricter hunting control, and in 1930 hunting quotas related to the size of the wild reindeer areas were introduced. The Ministry of Agriculture decided the number of licences, and the number of wild reindeer increased. During the 1950s a major controversy between the Ministry and local people arose in the Snøhetta area. People there increased their power over the wild reindeer management by organising a "Wild Reindeer Board" (WRB). This inspired people in other districts to organise similar boards. These WRBs had no formal power according to the law, but became important managers of the herds. An official organisation for each wild reindeer area, the Wild Reindeer Committee (WRC), was introduced in 1988. Since the WRCs are official institutions, legal power is decentralised to them.
Keywords: wild reindeer management; Norway; co-management; common pool resources; Rangifer tarandus; Rondane; Snøhetta